Critique and Postcritique - Felski, Rita, 1956-; Anker, Elizabeth S. (Elizabeth Susan), 1973- (Book collections on Project MUSE., 2017)
The contributors to Critique and Postcritique evaluate literary critique's structural, methodological, and political potentials and limitations while assessing the merits of the post-critical turn and exploring a range of alternate methods of literary criticism that may be better suited to the intellectual and political challenges of the present.